2012
DOI: 10.17305/bjbms.2012.2514
|View full text |Cite
|
Sign up to set email alerts
|

Prostatic carcinoma bilateral iris metastases

Abstract: We described a patient with bilateral iris metastases resulted from prostatic cancer. Slit lamp and ultrasonography examination of the both eye demonstrated tumor of the iris, as an amelanotic vascular mass located on the superior temporal quadrant. On open biopsy revealed undifferentiated tissue that stained strongly positive for prostate carcinoma, confirming the diagnosis of metastasis prostate adenocarcinoma. Early diagnostic procedures are essential for the causal therapy of prostate carcinoma as the prim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…5 Adenocarcinoma of the prostate is implicated in 3.6% to 4% of all orbital metastases; among them, metastases to the uvea have been commonly reported. [6][7][8] In very rare cases, metastases to the external rectus muscle and the optic nerve tract have been indicated. 9 When the disease metastasizes to the orbit, symptoms such as decreased vision, impaired eye movement, diplopia, and increased intraocular pressure are observed due to compression of the intraorbital tissue.…”
Section: Discussionmentioning
confidence: 99%
“…5 Adenocarcinoma of the prostate is implicated in 3.6% to 4% of all orbital metastases; among them, metastases to the uvea have been commonly reported. [6][7][8] In very rare cases, metastases to the external rectus muscle and the optic nerve tract have been indicated. 9 When the disease metastasizes to the orbit, symptoms such as decreased vision, impaired eye movement, diplopia, and increased intraocular pressure are observed due to compression of the intraorbital tissue.…”
Section: Discussionmentioning
confidence: 99%
“…However, soft tissue metastasis to the orbit is extremely rare. Most cases of soft tissue orbital metastasis secondary to PC involve the uveal tract [ 13 - 17 ] ( Table 1 ). PC is the most common primary cancer to metastasize to the iris (uveal tract) and the reported incidence ranges from 8% to 10% [ 18 , 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…It was reported that breast cancer (1), prostate cancer (2), adenoid cystic carcinoma of parotid gland (3), lung cancer (4), merkel cell carcinoma (5), esophageal adenocarcinoma (6), gastric cancer (7), endometrial cancer (8), Ewing sarcoma (9) and cervical cancer (10) metastasized to iris.…”
Section: Introductionmentioning
confidence: 99%